EcoThin: Innovation of Plant-Based Biopolymer Food Packaging as a Strategy for Preventing Microplastic Pollution - Syarafina Khoirunnisa; Usamah; Ainun Azka Rohmatillah; Rizkiy Amaliyah Barakwan (ECOTON: Ecological Observation and Wetlands Conservation, 2026)
Indonesia faced a microplastic emergency in 2024, with average human intake reaching 15 g per month, the highest globally. Dominant polymers such as Polypropylene, High-density Polyethylene, and Polystyrene from single-use packaging were prevalent in the culinary sector and UMKM, underscoring the urgency for biodegradable alternatives. This study developed EcoThin, a food packaging film made from cassava starch, banana pseudostem fibers, and banana peel pectin as natural binder with glycerol as plasticizer and acetic acid as solvent. Films were produced using solvent casting and evaluated for sensory attributes, morphology, water uptake, and moisture content. The fiber–pectin ratio of 50:50 showed optimal performance, producing homogeneous, flexible films with improved water retention. EcoThin demonstrates potential as a biodegradable substitute for plastic packaging, supports the prevention principle in solid waste management, offers applicability to UMKM in the culinary sector, and contributes to SDG 12 on responsible consumption and production.